2005
DOI: 10.1159/000083281
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Biofeedback Relaxation of the Pelvic Floor in Treating Pediatric Dysfunctional Voiding: A Short-Course Program Is Effective

Abstract: Introduction: We report the treatment results of a short course of biofeedback relaxation of the pelvic floor (BRPF) in treating children with dysfunctional voiding. Materials and Methods: Fourteen girls and 6 boys with videourodynamically proved dysfunctional voiding were enrolled. To increase the awareness of the abnormal voiding pattern, the anatomy of the pelvis and the results of a voiding diary and videourodynamics were extensively explained to the patients/parents. Surface electromyography and uroflowme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Using biofeedback techniques is another possibility, giving a similar outcome [19,20]. The success rate in our setting of VS was after a year about the same (76%), showing that urotherapy in groups of children is a good alternative to individiual urotherapy.…”
Section: Discussionmentioning
confidence: 67%
“…Using biofeedback techniques is another possibility, giving a similar outcome [19,20]. The success rate in our setting of VS was after a year about the same (76%), showing that urotherapy in groups of children is a good alternative to individiual urotherapy.…”
Section: Discussionmentioning
confidence: 67%
“…This disorder is frequently associated with overactive bladder and the treatment is biofeedback. 3,4 We found that 75% of patients had urinary incontinence data, which is very difficult to obtain because generally the urine leak is unnoticed by the patient or caregiver because the small amount of urine is mixed with the vaginal discharge. As mentioned before, there are patients who have no symptoms and still have altered urodynamics, as was reported in two cases.…”
Section: Discussionmentioning
confidence: 97%
“…The patient was taught modified voiding habits and how to use BFB once a day at home between each session. 4 All patients were revaluated by a pediatric gynecology after three months. A total or partial remission of inflammatory symptoms and ceased vaginal discharge was considered a positive response.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of bladder disturbances utilizes EMG tracing of PFM contraction and relaxation visualized in the form of an animation tailored for children, or a simple uroflow curve [56, 57]. Bower et al reported a success rate of 90 % for children with DV who followed a half-day urotherapy program which included uroflow biofeedback and instruction on the relaxation of PFM [58]. Animated biofeedback programs which involve computer games are particularly suitable for children and enable faster resolution of symptoms when compared to non-animated methods [59].…”
Section: Day Wettingmentioning
confidence: 99%